Семантика и сочетаемость польских и русских имен прилагательных с суффиксом „-liw-”/„-лив-” - Kuligowska, Katarzyna (Studia Rossica Posnaniensia, 2015)
The author analyzes the different shades of meaning and the semantic valency of Polish and Russian adjectival derivatives with the suffix -liw- /-лив-. The words that are studied here exhibit an anthropocentric orientation as they principally describe natural human inclinations and collocate with personal nouns. Semantically impersonal adjectives are sparse among the analyzed lexemes in both languages.